BioEssays 6/2020. (25th May 2020) - Liu, Yang; Wang, Baojun
Abstract : CRISPR activation (CRISPRa) in bacteria is an attractive method for programmable gene activation. In article number 1900252, Yang Liu and Baojun Wang summarize the current state‐of‐the‐art in this area of high potential, and present the powerful features and capabilities of a newly reported eukaryote‐like, σ 54 ‐dependent CRISPRa system. The eukaryote‐like bacterial CRISPRa enables novel designs in synthetic gene regulation and promotes research in the σ 54 ‐dependent gene networks with broad applications envisioned.